The contribution of executive functions and emotion comprehension skills to the development of pragmatic competence in 5–8-year-old children - Oshchepkova, Ekaterina; Shatskaya, Arina; Tarasova, Kristina (Frontiers in Psychology, 2025)
A child’s pragmatic competence reflects both their social and communicative abilities, as well as their understanding of indirect meaning in words, utterances or discourse. This has led to a growing interest in the development of pragmatics in children. While the contribution of cognitive and emotional developmental aspects to pragmatic competence in general has been explored, the role of the emotion comprehension (EC) and executive functions (EF) in different pragmatic skills is still insufficiently studied. The purpose of this study was to investigate the impact of children’s EF, and EC skills, on four core aspects of pragmatic competence (understanding, production, nonverbal means and communication). Participants were children (N = 1,842) aged 59–96 months (M = 73.51, SD = 9.0) and their teachers. Children completed tests assessing their EF (NEPSY-II) and understanding of emotions (Test of Emotion Comprehension), and their teachers completed a questionnaire of the children’s pragmatic competence. Through comparison of baseline and extended regression models, it was shown that although EF contribute significantly to all aspects of pragmatic competence, the connections with EC remain at a correlational level. Their contribution to pragmatic competence is not confirmed. These findings can support the development of programs to enhance children’s pragmatic competence, targeting educators, parents, and the children themselves.